Node‐by‐node diagnosis for multiple ipsilateral nodules by segmental adrenal venous sampling in primary aldosteronism. (21st December 2022) - Tannai, Hiromitsu; Makita, Kohzoh; Koike, Yuya; Kubo, Haremaru; Nakai, Kazuki; Yamazaki, Yuto; Tsurutani, Yuya; Saito, Jun; Matsui, Seishi; Kakuta, Yukio; Sasano, Hironobu; Nishikawa, Tetsuo
Abstract: Objectives: In patients with primary aldosteronism (PA), multiple adrenocortical nodules may be present on the surgical side. The aim of this study was to clarify the pathological diagnosis and the node‐by‐node diagnostic capability of segmental adrenal venous sampling (sAVS). Design: Retrospective study. Patients: A total of 162 patients who underwent adrenalectomy following sAVS were studied. Measurements: Multiple nodules on the surgical side were extracted while referring to contrast‐enhanced computed tomography images. We also performed a detailed histopathological analysis of the resected specimens from patients undergoing sAVS, which included immunohistochemistry for CYP11B2. Results: In 11 (6.8%) patients, two to three nodules were detected on the surgical side. All patients were diagnosed by sAVS with at least one aldosterone‐producing adenoma (APA) for localized aldosterone elevation in tributaries. Seven patients showed a lateralization index value of ≥4 after ACTH stimulation. Histopathologically and clinically, two patients had two or three CYP11B2‐positive APAs, and the other nine patients both APAs and non‐APAs. The positive predictive value of the most suspected APA, that is, the drainer that showed the highest aldosterone level by sAVS, was 11/11 (100%, 95% confidence interval [CI]: 71.5%–100%), while that for the second and third suspected APA was 3/7 (42.9%, 95% CI: 9.9%–81.6%), and they were significantly different ( p  = .01). Further, the positive predictive value of non‐APA was 4/4 (100%, 95% CI: 39.8%–100%). Conclusions: The sAVS could correctly diagnose the aldosterone production in multiple ipsilateral adrenal nodules.